Parenting style and depression among students: The mediating role of self-esteem - Jannah, Kholifatul; Hastuti, Dwi; Riany, Yulina Eva (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Parenting style has been highlighted as one of the causes of depressive symptoms and also influences adolescent self-esteem. Although many studies have investigated the effect of self-esteem on depression, few have considered its role as a mediator variable. Therefore, this study aims to analyze the direct effect of parenting style on adolescent depression and its indirect effect on self-esteem. An online survey was completed voluntarily by 555 respondents from four senior high schools in Bekasi, Indonesia. The Patient Health Questionnaire, Parental Authority Questionnaire, Rosenberg Self-esteem Scale, and Path-SPSS analysis were employed to prove the hypothesis. The results show a significant direct effect of parenting [authoritative (β = -.257, p < .01), authoritarian (β = .181, p < .01) and permissive (β = .109, p < .01)] on depression. In addition, there is an indirect effect of authoritative (β = -.182, p < .01) and authoritarian (β = .055, p < .01) parenting styles on depression as mediated by self-esteem. The study indicates the importance of positive parenting and the building of adolescents' self-esteem to avoid the risk of depression.